EFFECTS OF EXOGENOUS PROTEASE SUPPLEMENTATION IN PALM KERNEL MEAL-BASED DIETS ON GROWTH PERFORMANCE AND HEALTH CONDITION OF PACIFIC WHITE SHRIMP (Penaeus vannamei) CULTURED IN HAPA NETS - Romi Novriadi; Mila Wahyuningsih; I Gusti Ngurah Permana; Ketut Mahardika; Didi Widjaya; Nguyen Ngoc Binh; Hervé Lucien- Brun (Indonesian Aquaculture Journal, 2026)
The effect of exogenous protease complex (Jefo Protease, Jefo Nutrition Inc., Saint-Hyacinthe, QC, Canada) was investigated for 90 days on the forty hapa nets (2 m × 2 m × 1 m, 200 shrimps per hapa net) with five replicates for each treatment groups to the growth, health condition, and also histological condition of the distal intestine and hepatopancreas of the shrimp Penaeus vannamei. Treatments were generally grouped into feed groups supplemented with protease and without protease. The first diet in the protease group was formulated using 40% soybean meal (SBM) and supplemented with protease (0JPKM). Then, the following three experimental feeds were formulated with reduced inclusion levels of SBM, replaced with 5, 10, and 15% palm kernel meal (PKM), supplemented with protease, and labeled as 5, 10, and 15 JPKM. For feed without protease, a similar formulation was used as the protease group without adding protease and labeled as 0, 5, 10, and 15% PKM. In our study, adding protease improved shrimp growth performance; even the inclusion of 5% PKM to replace SBM supplemented with protease (5JPKM) had the same growth as the shrimp fed with SBM without protease (0 PKM). Data on the total hemocyte count (THC) of shrimp showed an increase in the group with protease supplementation compared to those without protease supplementation. Meanwhile, lysozyme activity did not significantly differ. Histomorphology evaluation data in the hepatopancreas and intestine of shrimp showed better morphology in shrimp supplemented with protease compared to the group of shrimps that were not supplemented with protease. These results show that protease supplementation in feed protease with an inclusion level of 0.18% could significantly improve growth performance, THC, and digestion in P. vannamei shrimp.